COX‐2, mPGES‐1 and EP2 receptor immunohistochemical expression in canine and feline malignant mammary tumours. (14th May 2014) - Millanta, F.; Asproni, P.; Canale, A.; Citi, S.; Poli, A.
Abstract: Prostaglandin (PG) signalling is involved in human and animal cancer development. PG E2 (PGE2 ) tumour‐promoting activity has been confirmed and its production is controlled by Cyclooxygenase‐2 (COX‐2) and microsomal PGE synthase‐1 (mPGES‐1). Evidence suggests that mPGES‐1 and COX‐2 contribute to carcinogenesis through the EP2 receptor. The aim of our study was to detect by immunohistochemistry COX‐2, mPGES‐1 and EP2 receptor expression in canine ( n  = 46) and feline ( n  = 50) mammary tumours and in mammary non‐neoplastic tissues. COX‐2 positivity was observed in 83% canine and 81% feline mammary carcinomas, mPGES‐1 in 75% canine and 66% feline mammary carcinomas and the EP2 receptor expression was observed in 89% canine and 54% feline carcinomas. The frequency of COX‐2, EP2 receptor and mPGES‐1 expression was significantly higher in carcinomas than in non‐neoplastic tissues and adenomas. COX‐2, mPGES‐1 and EP2 receptor expression was strongly associated. These findings support a role of the COX‐2/PGE2 pathway in the pathogenesis of these tumours.